SHORT SYNTHESIS OF A BICYCLIC MIMIC OF ALPHA-L-FUCOSE - Beacham, A; Biggadike, K; Taylor, H; Hackett, L; Winchester, B; Watkin, D; Fleet, G (1994)
The stability of a 2,7-anhydroheptulose, readily available from L-gulonolactone, may provide clues to a wide range of bicyclic analogues of conformationally fixed α-L-fucose.